Genetics, Screening, and Treatment of Familial Hypercholesterolemia: Experience Gained From the Implementation of the Vietnam Familial Hypercholesterolemia Registry - Truong, Thanh-Huong; Do, Doan-Loi; Kim, Ngoc-Thanh; Nguyen, Mai-Ngoc Thi; Le, Thanh-Tung; Le, Hong-An (Frontiers in Genetics, 2020)
Familial hypercholesterolemia (FH) is under-diagnosed and under-treated in a majority of the low- and middle-income countries. FH registries could prove useful in bridging the knowledge gaps, support genetic and clinical research, and improve healthcare planning and patient care. Here, we report the first usage experience of the Vietnam FH Registry (VINAFH). The VINAFH Registry was established in 2016 as a long term database for prospective cohorts. FH patients were detected based on the opportunistic and cascade screening. Diagnosis of FH was assessed using the Dutch Lipid Clinic Network criteria, plasma levels of low-density lipoprotein (LDL) cholesterol, and genetic testing. To date, a total of 130 patients with FH have been registered, with 48 index cases and 82 relatives. Of the 130 patients, 8 were homozygous FH patients and 38 were children. In 46.7% of FH individuals was confirmed by genetic testing: 61 patients (96.8%) carried the LDLR mutation (c.681C>G, c.1427C>G, c.1187-?_2140±?del, c.2529_2530delinsA) and two patients (3.2%) carried the PCSK9 (protein convertase subtilisin/kexin type 9) mutation (c.42_43insTG). The c.2529_2530delinsA mutation detected in this study is novel, and reported only in Vietnamese population. However, only 53.8% of FH patients were followed-up post-diagnosis, and only 15.3% of these were approved for lipid-lowering therapy and specialized care. Notably, factors such as knowledge about FH in patients and/or guardians of FH children and support of primary care physicians affected patient participation with respect to treatment strategies and follow-up. Genetic identification, screening, and treatment of FH were feasible in Vietnam. The VINAFH Registry significantly contributed to the formation of the government agencies legislative acts that established the importance of FH as a socially and medically important disease requiring appropriate management strategies. Other low- and middle-income countries could, thus, use the VINAFH Registry model as a reference to establish programs for FH management according to the current status.